ANALISIS BIBLIOMETRIK ENTREPRENEURSHIP KORPORAT PADA BASIS DATA SCOPUS - Purnomo, Margo; Ginanjar*, Jajang; Purbasari, Ratih; Paramita, Bunga; Nurdin, Mahmud (JURISMA : Jurnal Riset Bisnis & Manajemen, 2022)
Corporate Entrepreneurship (CE) has become an interesting area of ​​academic research today. This study aims to systematically analyze global trends and various current focus of CE research on CE and is expected to be a reference for CE researchers. The data is taken from the Scopus database with a time span of 2010-2020. Data were processed with Excel 2016 to analyze the main features of CE studies, including annual publication trends, authors, author's institution and country of origin, journals, references, and keywords. Data processing is then mapped visually using VOSviewer. The results of this study can provide a clear picture of the field of EK as well as can help academics to get focus on the direction of EK research in terms of exploitation and exploration in this field for future research. Keywords: Corporate Entrepreneurship, Bibliometric, VOSviewer, Scopus, Literature Review